2009
DOI: 10.3899/jrheum.090360
|View full text |Cite
|
Sign up to set email alerts
|

Progress on Incorporating the Patient Perspective in Outcome Assessment in Rheumatology and the Emergence of Life Impact Measures at OMERACT 9

Abstract: The Patient Perspective Workshop included over 100 researchers and 18 patient participants from 8 countries. Following preconference reading and short plenary presentations, breakout groups considered work undertaken on measurement of sleep, assessing interventions to develop the effective consumer, and assessing psychological and educational interventions. The workshop explored the best way to identify other outcome domains (and instruments) that should be measured in observational or interventional studies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
188
0
6

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 163 publications
(199 citation statements)
references
References 7 publications
5
188
0
6
Order By: Relevance
“…Even with the large number of PROs available, some patient-reported domains, such as body image, are not being reported in recent publications. There are few studies in PsA aiming to know which domains are considered the most important in patients' opinions (12,106). Fatigue is a patient-reported domain described in only 15.5% of PsA articles.…”
Section: Discussionmentioning
confidence: 99%
“…Even with the large number of PROs available, some patient-reported domains, such as body image, are not being reported in recent publications. There are few studies in PsA aiming to know which domains are considered the most important in patients' opinions (12,106). Fatigue is a patient-reported domain described in only 15.5% of PsA articles.…”
Section: Discussionmentioning
confidence: 99%
“…While early studies on RA fatigue exist (6 -10), it is only over the last decade that fatigue in IA has become a variable of interest among rheumatology researchers and clinicians (11,12). This development occurred when the established international consensus conference Outcome Measures in Rheumatology (OMERACT) invited patients to become research partners (11,13,14). Following this OMERACT initiative, fatigue secured its place on the rheumatology research agenda internationally (11,13).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the field of RA outcomes research has moved forward. New insights into the relationship between disease activity, joint damage, and disability have been put forward (8 -10), new indices or criteria have been proposed following patients in practice and/or trials (11)(12)(13), and an expansion of patientreported outcomes (PRO) has been suggested (14,15). Finally, new and highly effective recently approved drugs, such as inhibitors of tumor necrosis factor ␣ (TNF␣) and other biological agents in combination with methotrexate, have challenged outcomes assessment by their relatively rapid onset of action, their profound efficacy, and other aspects related to their clinical effectiveness (16).…”
Section: Introductionmentioning
confidence: 99%